Analytical and numerical investigation of the length of the cohesive zone in delaminated composite materials - Albert Turon (2008)
An accurate prediction of the length of the cohesive zone ahead of a crack tip is fundamental for the correct simulation of delamination in composite materials under both quasi-static and fatigue loading. To ensure a correct dissipation of energy during delamination propagation, several cohesive finite elements have to span the cohesive zone. The length of the cohesive zone depends on the material properties, the geometry/size of the structure, and on the loading mode. This chapter presents new expressions to estimate the length of the cohesive zone under general mixed-mode loading conditions and for finite-sized geometries. The analytical model is validated by comparing its predictions with numerical results based on cohesive-zone models. The relevance of the proposed analytical solutions to the effective simulation of delamination is demonstrated by simulating delamination growth under mixed-mode loading using meshes with the length of the elements greater than the cohesive zone length.